Mangiferin Ameliorates Cisplatin Induced Acute Kidney Injury by Upregulating Nrf-2 via the Activation of PI3K and Exhibits Synergistic Anticancer Activity With Cisplatin - Sadhukhan, Pritam; Saha, Sukanya; Dutta, Sayanta; Sil, Parames C. (Frontiers in Pharmacology, 2018)
Occurrence of oxidative stress is the principal cause of acute kidney injury induced by cisplatin. Mangiferin, a naturally occurring antioxidant molecule, is found to ameliorate several oxidative stress mediated pathophysiological conditions including cancer. Cisplatin induced cytotoxicity was measured in NKE cells by MTT assay and microscopic analysis. Induction of oxidative stress and regulation of proapoptotic molecules were subsequently investigated by using different spectrophotometric analyses, FACS and immunocytochemistry. Induction of nephrotoxicity was determined by analyzing different serum biomarkers and histological parameters in vivo using swiss albino mice. Activation of NF-κB mediated pro-inflammatory and caspase dependent signaling cascades were investigated by semi-quantitative RT-PCR and immunoblotting. Mangiferin was found to ameliorate cisplatin induced nephrotoxicity in vitro and in vivo by attenuating the induction of oxidative stress and upregulating Nrf-2 mediated pro-survival signaling cascades via the activation of PI3K. Additionally, mangiferin showed synergistic anticancer activity with cisplatin in cancer cell lines (MCF-7 and SKRC-45) and EAC cell induced solid tumor bearing experimental mice. The ameliorative effect of mangiferin is primarily attributed to its anti-oxidant and anti-inflammatory properties. It acts differentially in normal tissue cells and tumor cells by modulating different cell survival regulatory signaling molecules. For the first time, the study reveals a mechanistic basis of mangiferin action against cisplatin induced nephrotoxicity. Since Mangiferin shows synergistic anticancer activity with cisplatin, it can be considered as a promising drug candidate, to be used in combination with cisplatin.